2011
DOI: 10.1177/1359105310383605
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer patients’ topic avoidance and psychological distress: The mediating role of coping

Abstract: Avoiding communication about cancer is common and is likely to have negative psychological health consequences for patients, yet the connection between topic avoidance and psychological well-being is not well understood. This study of women with breast cancer examined coping behaviors as mediating mechanisms through which their cancer-related topic avoidance might affect their psychological distress. Consistent with predictions, greater levels of patient topic avoidance were associated with higher levels of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 41 publications
4
50
1
4
Order By: Relevance
“…It is assumed that people who view their cancer as having already caused a great amount of loss engage in escape and avoidance behaviors in an effort to turn their attention away from the situation (Franks & Roesch, 2006). A vast amount of literature is congruent with our findings regarding the use of escape-avoidance coping and depression in cancer patients (Costanzo et al, 2006; Donovan-Kicken & Caughlin, 2011). Escape and avoidance may provide temporary relief from dealing with the stress of cancer; however, they do not change the outcome of the situation; if that is the goal, then efforts to cope in this manner will be futile.…”
Section: Discussionsupporting
confidence: 84%
“…It is assumed that people who view their cancer as having already caused a great amount of loss engage in escape and avoidance behaviors in an effort to turn their attention away from the situation (Franks & Roesch, 2006). A vast amount of literature is congruent with our findings regarding the use of escape-avoidance coping and depression in cancer patients (Costanzo et al, 2006; Donovan-Kicken & Caughlin, 2011). Escape and avoidance may provide temporary relief from dealing with the stress of cancer; however, they do not change the outcome of the situation; if that is the goal, then efforts to cope in this manner will be futile.…”
Section: Discussionsupporting
confidence: 84%
“…Findings also suggested that family communication problems may cause a lack of initiative to cope with their problems and lead a decrease in coping use. Consistent with previous research [39], family communication strain was associated with poor mental health. As shown in previous research [8, 40], external family coping such as marshaling support from friends/relatives and spiritual support appears to help Chinese- and Korean-American BCS adapt positively, leading to better mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Effective communication positively influences the rate of patient recovery, pain control, adherence to treatment regimens, psychological functioning, and quality of life (e.g., Gattellari et al, 2001; Uitterhoeve et al, 2009; Vogel et al, 2009). Alternatively, ineffective communication can leave patients feeling anxious, and is associated with increased uncertainty and dissatisfaction with care (Hagerty et al, 2005), increase lack of compliance with recommended treatment regimens (Jin et al, 2008; Martin et al, 2005), and elevated rates of depression and anxiety (Donovan-Kicken and Caughlin, 2011). As well, ineffective communication may negatively affect the nurses by increasing stress, lack of job satisfaction, and emotional burnout (e.g., Emold et al, 2010; Potter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%